2000
DOI: 10.1056/nejm200011303432207
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Policies on Disclosure of Conflicts of Interest in Biomedical Research

Abstract: There is substantial variation among policies on conflicts of interest at medical schools and other research institutions. This variation, combined with the fact that many scientific journals and funding agencies do not require disclosure of conflicts of interest, suggests that the current standards may not be adequate to maintain a high level of scientific integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(98 citation statements)
references
References 15 publications
0
93
0
5
Order By: Relevance
“…Kevin Haggerty identifies a global increase in ethical regulation of research in the humanities, and refers to this phenomenon as an 'ethics creep' (Haggerty 2004): a system of pre-emptive and post-fact ethical regulation that is becoming a major threat to research in the humanities and social sciences. This type of regulation has been transplanted to the humanities from the biomedical sciences, where ethical regulation became significant in the aftermath of the Holocaust and the Nuremberg trials (see Dingwall 2008;Jacob and Riles 2007;Resnik 2009); the adoption of ethical regulations in biomedical research has by now become standard practice in most institutions worldwide (Brody 1998;CIOMS 2002;McCrary et al 2000;Steneck 2007). However, scholars like Dingwall, Haggerty, Schrag and others point out that research in the humanities, with the exclusion of research in psychology or research that involves minors or at-risk individuals, seldom involves irrevocable interventions or is likely to cause harm to the extent that these things are possible in biomedical research (see also Gunsalus et al 2005;Hamburger 2004;Jacob and Riles 2007).…”
Section: Ethical Regulation In the Humanitiesmentioning
confidence: 99%
“…Kevin Haggerty identifies a global increase in ethical regulation of research in the humanities, and refers to this phenomenon as an 'ethics creep' (Haggerty 2004): a system of pre-emptive and post-fact ethical regulation that is becoming a major threat to research in the humanities and social sciences. This type of regulation has been transplanted to the humanities from the biomedical sciences, where ethical regulation became significant in the aftermath of the Holocaust and the Nuremberg trials (see Dingwall 2008;Jacob and Riles 2007;Resnik 2009); the adoption of ethical regulations in biomedical research has by now become standard practice in most institutions worldwide (Brody 1998;CIOMS 2002;McCrary et al 2000;Steneck 2007). However, scholars like Dingwall, Haggerty, Schrag and others point out that research in the humanities, with the exclusion of research in psychology or research that involves minors or at-risk individuals, seldom involves irrevocable interventions or is likely to cause harm to the extent that these things are possible in biomedical research (see also Gunsalus et al 2005;Hamburger 2004;Jacob and Riles 2007).…”
Section: Ethical Regulation In the Humanitiesmentioning
confidence: 99%
“…Se estima que el 50% de las revistas médicas con alto factor de impacto poseen sus propias normas sobre la declaración de conflictos de intereses (16). Algunas tienen normas muy rigurosas y exigen a los autores que declaren toda actividad remunerada en una sociedad privada (que tenga o no alguna relación con el artículo que desea publicar); otras exigen también que se declare la relación financiera que pueda existir entre la esposa o el esposo del autor(a) y la sociedad privada(19).…”
Section: Los Conflictos De Interés Y Las Publicacionesunclassified
“…Las soluciones no son tan simples, porque algunas personas piensan que la asociación industriauniversidad es fundamental para los avances de la medicina (16).…”
Section: Los Conflictos De Interés Y Las Publicacionesunclassified
“…However, in spite of multiple guidelines, in a survey of medical schools in the United States in 2000, 6% reported no policies on conflict of interests; and although 91% had developed policies that followed the federal thresholds for disclosure, the policies varied greatly in scope and requirements for disclosure. 60 In fact, only 1% required disclosure of conflicts to institutional review boards. Additionally, this survey demonstrated that only 43% of journals had policies requiring disclosures of conflict of interest.…”
Section: Management Of Conflict Of Interestmentioning
confidence: 99%